Infantile Onset Hypertrophic Cardiomyopathy Secondary to PRKAG2 Gene Mutation is Associated with Poor Prognosis - Gorla, Sudheer R.; Raja, Kishore R.; Garg, Ashish; Barbouth, Deborah S.; Rusconi, Paolo G. (Journal of Pediatric Genetics, 2018)
Hypertrophic cardiomyopathy (HCM) is the second most prevalent form of cardiomyopathy in children. The etiology of the HCM is heterogeneous, so is the age of onset of symptoms. The HCM associated with metabolic disorders and genetic syndromes presents early in childhood. There are very few case reports of early-onset infantile HCM secondary to the PRKAG2 gene. Here, we report a case of HCM in a neonate diagnosed prenatally and eventually diagnosed with a missense mutation in the PRKAG2 gene.
Keywords: Infantile Hypertrophic Cardiomyopathy; PRKAG2 gene mutation; worse outcome